Taxation, Saving, and the Rate of Interest - Boskin, Michael J. (Journal of Political Economy, 1978)
This study presents new estimates of consumption functions based on aggregate U.S. time-series data. The results are striking: a variety of functional forms, estimation methods, and definitions of the real after-tax rate of return invariably lead to the conclusion of a substantial interest elasticity of saving. The implications of this result for the analysis of the efficiency and equity of the current U.S. tax treatment of income from capital are explored. In reducing the real net rate of return, current tax treatment significantly retards capital accumulation. This in turn causes an enormous waste of resources and redistributes a substantial fraction of gross income from labor to capital. Rough estimates of the loss welfare exceed 50 billion per year (a present value close to 1 trillion!) and of the redistribution from labor to capital exceed one-seventh of the capital's share of gross Income.It also suggests that the usual calculations of tax burdens by income class substantially overestimate both the progressivity of the income tax and the alleged regressivity of consumption taxes.